(untitled) (Journal of Pharmaceutical Negative Results, 2023)
GC-MS is the best sensitive technique used for separation and identification of the many structurally complex components that are present in plant extracts. The present study was aimed to find the bioactive compounds present in the ethanol, aqueous, methanol and hexane extracts of leaf of Euphorbia hirta Linn. by qualitative, quantitative photochemical screening, Gas chromatography and mass spectrometry analysis. Aqueous, ethanol and methanol extracts of Euphorbia hirta leaves showed the presence of tannin, saponin, steroids, terpenoids, flavonoids, triterpenoids, polyphenol, glycoside, anthocyanins and coumarins). Hexane extract of Euphorbia hirta leaves showed the presence of steroids, terpenoids, polyphenol and anthroquinone were present.On the basis of qualitative analysis, the rich content of phytochemicals present in ethanol extract as compared to other extract and used for subsequent studies. Significant amount of flavonoids, total phenol, terpenoids and saponin present in Euphorbia hirta leaves. The prevailing compounds are Diethyl Phthalate, Phthalic acid, n-Hexadecanoic acid, 9,12Octadecadienoic acid, Gamma.-Sitosterol, Cholest-5-en-3-ol (3.beta.), beta.-Sitosterol, 4,4,6a,6b,8a,11,11,14b-Octamethyl-1,4,4a,5,6 and Octasiloxane, 1,1,3,3,5,5,7,7,9,9,11,11,13,13 15,15-hexadecamethyl were found to be in this extract. Based on the results obtained in the present investigation, it may be concluded that the biological activities of the identified phytocomponents used for anti-microbial, anti-inflammatory, antioxidant, anti-diabetic, anti-ulcer, hepatoprotective, antiarthritic hyporcholesterolemic, and anti-cancer activities. Therefore, Euphorbia hirta leaves is recommended as a source of phytopharmaceutical value.